Rancang Bangun Mesin Penepung Pakan Ternak Multifungsi Untuk Kelompok Tani Berkah Mandiri - Mayana, Hendri Candra; Mulyadi, Mulyadi; Nofriadi, Nofriadi; Z, Dito Farizal; Putri, Elsy Kumala (Politeknik Negeri Padang, 2024)
Animal feed is one of the essential components supporting livestock growth and development. High-quality feed can significantly enhance farm productivity. However, in the preparation of feed in powdered form, efficient machinery is often required to process raw materials into fine particles. This study aims to design and develop a multifunctional animal feed grinder capable of processing various raw materials, such as corn, rice husks, oil palm fronds, wild grass, and straw, into fine powder. The machine is designed with a power output of 4,856.95 watts, utilizing a 6.5 HP gasoline engine, and has a production capacity of 11.34 kg/hour at 3,600 rpm. The trial results demonstrated the machine's production capacity for each material per hour: corn at 32.2 kg, rice husks at 22.9 kg, oil palm fronds at 30.2 kg, wild grass at 16.5 kg, and straw at 10.8 kg. This multifunctional grinder is expected to assist farmer groups in processing animal feed more efficiently and effectively.